ABOUT EXPANSION OF TERRESTRIAL RADIOPHYSICAL METHODS FOR DETECTION OF ULTRA-HIGH-ENERGY COSMIC RAY - Kozhukhar, V. B.; Lytvynenko, I. O.; Lytvynenko, O. A. (Одеські астрономічні публікації, 2013)
Low arrival density of the ultra-high- energy cosmic rays is one of the main obstacles of their experimental research. Overcoming this problem was based on the increase in the sensitive area of terrestrial facilities. Currently, the area of such installations reached a practical limit. The further development of researches is connected with remote registration of accompanying electromagnetic radiation. The projects of remote sensor installation on space vehicles are known. In this work the opportunity of use of ground-based radio telescopes and Moon, as return reflector, for global remote detection of electromagnetic bursts caused by space ultra-high-energy cosmic rays in an atmosphere of the Earth is considered.